2018
DOI: 10.3390/molecules23081836
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB2 Receptor Gene and Environmental Interaction in the Development of Psychiatric Disorders

Abstract: CB2 cannabinoid receptor (CB2R) gene is associated with depression. We investigated the gene-environment interaction between CB2R function and diverse stressors. First, anxiety-like behavior during chronic-mild-stress (CMS) was evaluated in C57BL/6JJmsSlc mice following treatment with CB2R agonist JWH015 or inverse-agonist AM630. Second, locomotor activity and anxiety-like behavior were measured following exposure to an immune poly I:C stressor. Gene expressions of HPA axis related molecules, Fkbp5, Nr3c1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 57 publications
0
14
1
Order By: Relevance
“…In addition, sham mice partially lacking CB2 showed an enhanced depressive‐like behaviour, suggesting an antidepressant function of CB2 under basal conditions. Accordingly, previous studies targeting CB2 with pharmacological tools or genetic deletion have also shown antidepressant effects of CB2 activation (Ishiguro et al., 2018; Liu et al., 2017). Moreover, sham mice partially lacking CB2 did not show cognitive deficits under basal conditions, as other studies have reported when this receptor was pharmacologically blocked (Busquets‐Garcia et al., 2013).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, sham mice partially lacking CB2 showed an enhanced depressive‐like behaviour, suggesting an antidepressant function of CB2 under basal conditions. Accordingly, previous studies targeting CB2 with pharmacological tools or genetic deletion have also shown antidepressant effects of CB2 activation (Ishiguro et al., 2018; Liu et al., 2017). Moreover, sham mice partially lacking CB2 did not show cognitive deficits under basal conditions, as other studies have reported when this receptor was pharmacologically blocked (Busquets‐Garcia et al., 2013).…”
Section: Discussionmentioning
confidence: 97%
“…CB 2 receptors located on neurons and microglia in the spinal cord contribute to central sensitization in OA [ 98 ]. CB 2 receptors might play a role in the several neurological diseases, such as Alzheimer disease [ 99 , 100 ], depression [ 101 , 102 ], Parkinson disease [ 103 ] or memory formation [ 104 , 105 ]. However, since CB 2 in the other than peripheral location has been investigated recently, more studies are needed to clarify its role in various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding CB 2, there is evidence that CB 2 gene polymorphisms and decreased expression are related to psychiatric disorders like schizophrenia, depression, anxiety, autism spectrum disorders, chronic stress and alcohol dependence [ 154 ]. Use of CB 2 agonists decreases anxiety-like behavior in animal models of chronic stress, whereas CB 2 antagonists exacerbate the symptomatology [ 154 ]. CB 2 -dependent effects on stress-related behavior may be due to its previously mentioned properties for the regulation of the HPA axis and the production of glucocorticoids [ 54 ].…”
Section: Endocannabinoids and Neurological Dysfunctionmentioning
confidence: 99%